Research on EPC Construction Mode of China Informatization Project - Xin, Guohua (Pacific International Journal, 2023)
EPC(Engineering, Procurement, Construction) has a history of decades in global development, has been introduced to China for more than 40 years, and is widely used in China's chemical, electric power, construction, energy, and other construction projects. With the development of informatization in China, the construction mode of informatization projects continues to evolve, and the EPC construction mode has also been applied and promoted in the informatization industry and has promoted the construction efficiency of informatization projects. The author analyzes and studies the development of EPC in China and the application and practice of EPC mode in informatization projects, and makes a case analysis through the EPC construction mode practice of informatization projects. Through the analysis and case study, the author provides reference and reference for the construction of informatization projects using EPC mode in the development of the digital economy in China.